Evaluating the Effectiveness of Image Processing in the Task of Detecting Moving Objects by an Optoelectronic Surveillance System - E. I. Mikhnionok; A. V. Khizniak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
The article considers the approach proposed by the authors to evaluate the effectiveness of image processing in detecting moving objects by an optoelectronic surveillance system. The variety of indicators currently used by researchers to assess the quality of image processing suggests that common approaches have not yet been developed. The application of specific indicators is determined by the features of the implemented approaches to the image processing, as well as the specifics of the task in the interests of which the processing is carried out. The problem considered by the authors, assessing the effectiveness of the developed image processing method in relation to the problem of detecting moving objects by an optoelectronic surveillance system, determines the need for its consideration in two directions. The first is from the point of view of the effectiveness of the implemented approaches to image processing in order to increase the peak signal-to-noise ratio. The second is, in terms of increasing the efficiency of the automatic detector, by reducing the level of its false alarm. At the same time, the need for additional determination of the probability of correct detection and the construction of detection curves is mandatory, since in their entirety they are generally accepted indicators of the quality of detection. The application of the proposed approach will allow further comparison of the quality of the developed image processing method with other similar methods, as well as evaluation of the work of newly developed ones.